The impact of the Chilean pension withdrawals during the Covid pandemic on the future savings rate. (September 2022) - Madeira, Carlos
Highlights: Chilean households consume a significant fraction of their public pensions. The covid pension withdrawals increased households' non-contributory wealth. These pension withdrawals may decrease the economy's saving rate by 1.7%. Further increases in solidarity pensions may decrease the saving rate even more. Abstract: Chile implemented pension withdrawals during the pandemic at a much larger scale than other OECD countries. Estimating a life cycle model with survey data, I find that households consume a significant fraction of their non-contributory pension wealth, implying a tradeoff between improving public pensions and increasing savings. Counterfactual simulations show that the pandemic pension withdrawals may decrease the future savings rate by 1.7%. Furthermore, policy reforms may decrease the aggregate savings rate by 0.2% for each percentage point of solidarity tax from current workers. The solidarity taxes increase substantially the pension income of poor retirees, but their effects decline over time.